A mini review on the abiotic factors that disrupt honeybee behavior and impede plant pollination - Abou-Shaara, Hossam; Staron , Martin (ENTOMOLOGIA HELLENICA, 2025)
Honeybees, Apis mellifera, play a crucial role in pollinating various plants. During their foraging age, many stressors can directly disrupt their ability to collect food from flowers. These behavioral disruptions can hamper the foragers’ ability to perform round trips between the hive and the flowers, and to visit flowers for collecting food, leading to pollination failure. Stressful environments with poor air quality, pesticide contamination, microplastics, high electromagnetic fields, high wind speeds, and temperature extremes can affect foraging round trips and flower visitation ability. Despite the importance of successful flight trips until landing on flowers for pollination, no specific studies have comprehensively discussed these environmental stressors in the light of behavioral disruptions. Therefore, this mini-review considers abiotic stressors with or without human interference that can cause such behavioral disruptions in the context of recent studies, and suggests new avenues for future research, which are crucial for pollination studies and global food security. Understanding pollination failure due to behavioral disruptions in forager honeybees caused by abiotic factors, even when the bees are seemingly healthy, is emphasized. This article provides a synthesis of important bodies of work related to the foraging ecology of honeybees.